Fast increase of postmortem fentanyl blood concentrations after transdermal application: A call to careful interpretation. (September 2019) - Reiter, Alonja; Mueller, Alexander; Otto, Benjamin; Anders, Sven; Falckenberg, Maja; Iwersen-Bergmann, Stefanie; Andresen-Streichert, Hilke
Highlights: Postmortem, individual increase of fentanyl and norfentanyl concentrations occurs. Increase is significant at 6–8 h postmortem for fentanyl and norfentanyl. Postmortem redistribution correlates with decrease of pH-values after death. Possible influence on postmortem increases by the physique of the patient. To discover intoxications, ratio of norfentanyl/fentanyl or cutoffs cannot be used. Abstract: Background: Interpretation of postmortem fentanyl concentrations after transdermal application remains a challenge. There are indications that fentanyl shows relevant postmortem redistribution. The aim of this study was to investigate the time course of these changes and to develop recommendations for toxicological case work. Material and method: Blood specimens were collected from palliative care patients who were treated with fentanyl transdermal patches. Antemortem reference samples (ethylenediaminetetraacetic acid (EDTA) and serum specimens) were collected at stable dose rates. Postmortem femoral venous blood specimens were collected at four postmortem time-points: 2 hpm (hours postmortem), 6–8 hpm, 11–16 hpm and approximately 24 hpm. Liquid chromatography tandem mass spectrometry was applied to quantify fentanyl and norfentanyl. Results: Ten patients were included in the study (8 men, 2 women). Fentanyl patches with delivery rates of 12–150 μg/h were applied. Antemortem fentanyl levels in EDTA samples varied between 0.19 and 4.64 μg/L. At 6 to 8 hpm, blood concentrations of fentanyl were already significantly ( p = 0.05 ) higher in postmortem samples compared to the paired antemortem reference. On average, the antemortem concentration (range: 0.19–4.64 μg/L) increased 3-fold within 6–8 hpm (range: 0.4–14.9 μg/L), and 5.5-fold within 24 hpm (range: 0.39–21.88 μg/L). Norfentanyl concentrations increased significantly ( p = 0.01 ) within 6–8 hpm, too. In half of the patients, norfentanyl concentrations were below fentanyl concentrations, antemortem as well as postmortem. Conclusion: Postmortem fentanyl concentrations increased quickly. As early as 6–8 h after death, postmortem concentrations differ significantly from antemortem ones. Our results strongly indicate that postmortem blood concentrations of fentanyl after transdermal application should be interpreted carefully.